Using the strategy of direct and independent education and their impact on the achievement of the intermediate stage of the Arabic language subject - Thajeel, Ass. Lect. Muthanna Fleih Hassan; Abd, Ass. Lect. Firas Abdullah (مجلة اداب ذي قار, 2022)
The current research aims to identify: - (the use of the strategy of direct and independent education and their impact on the achievement of the intermediate stage of the Arabic language subject) and to achieve the goal of the research, the following zero hypothesis was formulated: - 1- There is no statistically significant difference at the level of significance (0.05) between the mean scores of (the experimental group that is taught using the strategy of independent and direct education) 0 and the average scores of the control group that is taught using the traditional method in the Arabic language achievement test 0 - In order to achieve the goal of the current research, a sample of (90) students was approved for a community of (300) students, from the second grade students in the schools affiliated to the General Directorate of Education. - After achieving the achievement test experience, the results were processed statistically, as in the research tool represented by the pre and post tests, as the validity of the tool was confirmed after it was presented to a group of experts, and the stability coefficients of the tool were found by applying the Cowder-Richardson equation 0 - The results of the statistical analysis in the achievement test related to the basic zero chance showed that (there is a statistically significant difference in the achievement test at the level of (0.5) for students’ achievement in favor of the strategy of direct and independent education), and thus the null hypothesis is rejected and the alternative hypothesis is accepted. - The statistical results showed that there is a statistically significant difference that tends in favor of the independent education strategy, and then the direct education strategy, compared with the regular education method, and thus the null hypothesis is rejected and the alternative hypothesis is accepted.